2006
DOI: 10.1073/pnas.0609448103
|View full text |Cite
|
Sign up to set email alerts
|

Canopy leaf area constrains [CO 2 ]-induced enhancement of productivity and partitioning among aboveground carbon pools

Abstract: carbon allocation ͉ global change ͉ nitrogen availability ͉ pine plantation C urrent studies and modeling exercises indicate a very significant role for terrestrial ecosystems in sequestering carbon (C) and potentially mitigating increases in atmospheric CO 2 concentrations ([CO 2 ]) (1, 2), with forests contributing Ϸ80% of terrestrial net primary productivity (NPP) (3). Recent analysis (4) found a surprisingly consistent enhancement of NPP under elevated [CO 2 ] across closed-canopy temperate forest ecosyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 54 publications
6
78
1
Order By: Relevance
“…It was shown that the net primary production of plants is dependent on the leaf area index, which, in turn, is conditional upon nitrogen supply [40]. In our experiments simultaneous increase in nodule number, leaf area and SPAD readings was observed, so taking into consideration the relationship between nitrogen supply and plant productivity [40] it can be assumed that the larger area available for photosynthesis stems from higher nitrogen supply from the nodules. The water use efficiency (WUE) values after Nod factor treatment were worse than in the control group, however, suggesting that changes in the water balance were not detrimental to the plants.…”
Section: Discussionmentioning
confidence: 72%
“…It was shown that the net primary production of plants is dependent on the leaf area index, which, in turn, is conditional upon nitrogen supply [40]. In our experiments simultaneous increase in nodule number, leaf area and SPAD readings was observed, so taking into consideration the relationship between nitrogen supply and plant productivity [40] it can be assumed that the larger area available for photosynthesis stems from higher nitrogen supply from the nodules. The water use efficiency (WUE) values after Nod factor treatment were worse than in the control group, however, suggesting that changes in the water balance were not detrimental to the plants.…”
Section: Discussionmentioning
confidence: 72%
“…We show that the C/N ratio and total N were potentially important for predicting the variations in soil bacterial diversity, at least at the local scale, where soil pH varied relatively little (4.1 to 5.2) and was uncorrelated to bacterial diversity. Because at this site N acts as a resource that limits plant growth (16,52,60,63), it is not surprising that a positive correlation between total N and soil bacterial diversity emerged. The competitive stress for limited N may eliminate more bacteria from the communities than the increase of bacteria which are adapted to a lower-N environment.…”
Section: Discussionmentioning
confidence: 99%
“…Higher CO 2 concentrations generally decrease stomatal conductance (Ainsworth & Long 2005), potentially leading to lower transpiration and increased soil water availability (Gerten et al 2005;Gedney et al 2006). On the other hand, vegetation productivity increases with CO 2 (Norby et al 2005), which may cause more transpiration through larger leaf areas (McCarthy et al 2006). Vegetation structure and functioning also respond to other drivers, such as longer growing seasons in the north (Lucht et al 2002;Morales et al 2007).…”
Section: Introductionmentioning
confidence: 99%